2017
DOI: 10.1051/matecconf/201711201018
|View full text |Cite
|
Sign up to set email alerts
|

The effect of drilling parameters for surface roughness in drilling of AA7075 alloy

Abstract: Abstract. AA7075 aluminum alloy has been very popular significantly interest in the production of structural components in automotive and aviation applications due to its high strength, low density, good plasticity and better machinability comparable to many metals. Particularly, final products must have uniformly high quality to ensure essential safety standards in the aircraft industry. The optimization of hole quality which can variable according to tool geometry and drilling parameters is important in spit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…Comparing the research findings of Zhaoju et al [ 28 ], the present study proves that the best filler improves the surface roughness. Figure 10 a, b exhibits the morphology of BUE formed in a flank surface of the tool during drilling of AA7075/ 0 wt.% TiB 2 AMC at drilling speed of 1000 m/minute.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Comparing the research findings of Zhaoju et al [ 28 ], the present study proves that the best filler improves the surface roughness. Figure 10 a, b exhibits the morphology of BUE formed in a flank surface of the tool during drilling of AA7075/ 0 wt.% TiB 2 AMC at drilling speed of 1000 m/minute.…”
Section: Resultssupporting
confidence: 85%
“…Yasir et al [ 27 ] studied SiC and alumina reinforced Al 6061 fusion composite and reported that the wear resistance of 15 wt.% filler reinforced hybrid composite is better than that of 5 wt.% filler reinforced composite. Zhu et al [ 28 ] conducted a drilling of aluminum 2024-T351/titanium Ti6Al4V stack and studied the mechanism of chip formation. Krischner et al [ 29 ] conducted drilling on Al/SiG/Graphite hybrid composite and reported influencing factors on surface roughness.…”
Section: Introductionmentioning
confidence: 99%
“…However, the authors did not discuss their results to show the significant impact of process parameters on thrust force and torque. Yaşar et al [15] found that the 𝑅 𝑎 was more affected by the 𝑉 𝑐 followed by 𝑓 while the point angle showed less impact on the 𝑅 𝑎 . It was also discussed that high 𝑉 𝑐 and 𝑓 were responsible for higher 𝑅 𝑎 .…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the results of the present work prove that the Taguchi based grey fuzzy logic method can be effectively employed for the calculation of multi-response characteristics with a very small number of experimental trials and less time is required to attain an optimal setting for the thermal drilling process. In future, to further improve this drilling process and the knowledge gathered from this algorithm the authors intend to introduce other parameters into account (cutting speed, point angle and feed rate (Yaşar, Boy, & Günay, 2017)) as well as check against novel materials (additive manufacturing).…”
Section: Accepted Manuscriptmentioning
confidence: 99%